2020
DOI: 10.3390/sports8040056
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and Solutions for Team Sports Athletes in Isolation due to COVID-19

Abstract: In December of 2019, there was an outbreak of a severe acute respiratory syndrome caused by the Coronavirus 2 (SARS-CoV-2 or in China. The virus rapidly spread into the whole World causing an unprecedented pandemic and forcing governments to impose a global quarantine, entering an extreme unknown situation. The organizational consequences of quarantine/isolation are: absence of organized training and competition, lack of communication among athletes and coaches, inability to move freely, lack of adequate sunl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
232
0
26

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(266 citation statements)
references
References 51 publications
8
232
0
26
Order By: Relevance
“…In the present study, the FSI measurements indicated that patients deteriorated in terms of cognitive and social subscales while no significant difference was found with regard to the physical subscale during the pandemic. Knowledge of these factors may help MS patients in their struggle against their illnesses and in reducing their perceived stress [28][29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the FSI measurements indicated that patients deteriorated in terms of cognitive and social subscales while no significant difference was found with regard to the physical subscale during the pandemic. Knowledge of these factors may help MS patients in their struggle against their illnesses and in reducing their perceived stress [28][29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, detraining had an impact on caloric balance and metabolism (i.e., increase in body fat and decrease in muscle mass), resulting in expected modifications to sleep and diet practices. Not being able to use their body as they were used to, athletes and referees might have felt restless, experiencing somatic anxiety and negative mood (Jukic et al, 2020).…”
Section: Ce As a Career Change-eventmentioning
confidence: 99%
“…In the motor skills dimension, the lack of engagement in physical activity could have led to reductions in speed, technical accuracy, sensorimotor coordination, and movement flow (Tran et al, 2017;Jukic et al, 2020). There is evidence that only 2-4 weeks of training cessation can cause a significant and marked loss of performance in both active populations and elite athletes (see Sousa et al, 2019).…”
Section: Ce As a Career Change-eventmentioning
confidence: 99%
“…However, very little has been discussed about the fundamental role of PA and physiotherapy in this subset of patients during the lockdown [17]. Isolation at home can lead to poor nutrition, low sleep quality, reduced PA levels and sedentary habits with different negative consequences, such as increased body fat, decreased muscle mass, insomnia and depression [1,2,10,22,23]. Therefore, it is important to highlight these unwanted consequences of quarantine to develop and provide practical and useful recommendations.…”
Section: Introductionmentioning
confidence: 99%